Alginate-Based Biomaterials for Regenerative Medicine Applications - Sun, Jinchen (Materials (Basel), 2013)
Alginate is a natural polysaccharide exhibiting excellent biocompatibility and biodegradability, having many different applications in the field of biomedicine. Alginate is readily processable for applicable three-dimensional scaffolding materials such as hydrogels, microspheres, microcapsules, sponges, foams and fibers. Alginate-based biomaterials can be utilized as drug delivery systems and cell carriers for tissue engineering. Alginate can be easily modified via chemical and physical reactions to obtain derivatives having various structures, properties, functions and applications. Tuning the structure and properties such as biodegradability, mechanical strength, gelation property and cell affinity can be achieved through combination with other biomaterials, immobilization of specific ligands such as peptide and sugar molecules, and physical or chemical crosslinking. This review focuses on recent advances in the use of alginate and its derivatives in the field of biomedical applications, including wound healing, cartilage repair, bone regeneration and drug delivery, which have potential in tissue regeneration applications.